DEVELOPMENT OF A POWTOON ANIMATION VIDEO ON HYDROCARBON MATERIAL BASED ON JOYFUL LEARNING TO INCREASE THE LEARNING INTEREST OF HIGH SCHOOL STUDENTS - Auniillah, Fadia Hayya Tahta; Kamaludin, Agus; Rahmawan, Setia (Jurnal Pendidikan Matematika dan IPA, 2025)
Chemistry materials that are memorized and abstract in large quantities tend to make students bored and lack enthusiasm for learning. Video animation offers innovation to make learning fun and allow students to understand the material quickly. This research aims to create animation videos based on Joyful Learning principles related to hydrocarbon materials to enhance students' interest in learning. This research is R&D research using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), but is limited to the developing stage. Products are evaluated by material experts, media specialists, reviewers, and student responses. The tools used included product quality assessment sheets and student feedback forms. The assessment results of the animated video quality by material experts were 90%, with very good criteria, media experts rated it 95%, also with very good criteria, and reviewers scored it 92.5%, still with very good criteria. High school students in grade XI responded positively, with a 95% approval rate. The data suggests that the developed animated videos can serve as an alternative learning medium, enhancing students' interest in learning.